Healthcare Provider Characteristics and Cardiopulmonary Resuscitation Quality During Infant Resuscitation: A Simulation Study. Issue 2 (1st April 2022) - Khattab, Mona; Frisell, Karin; MacKinnon, Ralph; Chang, Todd; Raymond, Tia; Lofton, Lydia; Tofil, Nancy; Forrester, Katherine; Gohel, Charmin; Aitken, Deborah; Scalzo, Anthony; Moore-Clingenpeel, Melissa; et al.
Abstract : Introduction: Healthcare providers' anthropometric characteristics can adversely affect adult cardiopulmonary resuscitation (CPR) performance quality. However, their effects on infant CPR are unknown. We aimed to determine any relationships between healthcare provider characteristics (anthropomorphic, demographics, training, occupational data) and simulated infant CPR performance at multiple international sites. Our secondary aim was to examine provider's CPR performance degradation. Methods: Providers from 4 international hospitals performed 2 minutes of single-rescuer simulated infant CPR using 2015 American Heart Association Basic Life Support criteria with guidance from a real-time visual performance feedback device. Providers' characteristics were collected, and the simulator collected compression and ventilation data. Multivariate analyses examined the entire 2 minutes and performance degradation. Results: Data from 127 participants were analyzed. Although median values for all compression variables (depth, rate, lean) and ventilation volume were within guideline target ranges, when looking at individuals, only 52% chest compressions and 20% ventilations adhered to the American Heart Association guidelines. Age was found to be independently associated with ventilation volume (direct-relationship), and height was associated with chest compression lean (shorter participant-deeper lean). No significant differences were noted based on sex or body mass index. Neonatal intensive care unit participants were noted to perform shallower chest compressions ( P < 0.001). Overall, there was minimal evidence of performance degradation over 2 minutes. Conclusions: Isolated provider characteristics were noted among a diverse cohort of healthcare providers that may affect the CPR quality on a simulated infant. Understanding the relationships between provider characteristics and CPR quality could inform future infant CPR guidelines customized for the provider and not just the patient.